The Effect of Professional Skepticism, Auditor Experience, and the Application of Ethical Rules on Fraud Detection - Rivaldo Martua; Rifkiansyah Al Hafidz; Grace Angelica (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to analyze the effect of professional skepticism, auditor experience, and the application of ethical rules on the auditor’s ability to detect fraud. This study also aims to obtain empirical evidence regarding how these three factors can affect can effect the effetiveness of fraud detection. With a focus on auditors at Public Accounting Firms (KAP) in the Jakarta and Bekasi areas, this study is expected to provide useful insightsto improve audit quality and reduce the risk of fraud in financial statements. Design/methodology/approach – This study uses a qualitative method with a survey design. Data were collected through a 4-point Likert scale-based questionnaire distributed to internal and external auditors at the Public Accounting Firm (KAP) in the Jakarta and Bekasi areas. The research sample was taken using snowball sampling technique, with a total 105 respondens. Data analysis wa conducted using the Partial Least Square (PLS) method to test the relationship between professional skepticsm, auditor experience, application of etichal rules, and fraud detection. Findings – This study found that professional skepticsm, auditor experience, and the application of ethical rules have a significant positive effect on fraud detection. Auditors who are critical, experienced, and adhere to ethical rules show better ability to detect patterns of fraud. These three factors together improve audit quality and reability in detecting fraud . Research limitations/implications – This study was limited to auditor respondens in Bekasi and Jakarta using a questionnaire method, and focused on three main variables without considering others factors such as time pressure. The cross-sectional design also limits the analysis of changes over time. However, the results of this study provide important insights into the role of professional skepticsm, auditor experience, and the application of ethical rules in fraud detection, which can be utulized to improve audit practices and form the basis of future research.